The Effect of Fixed Asset Turnover on Return on Assets in Food and Beverage Sub-sector Companies Listed on the Indonesia Stock Exchange (2021–2024) - Wahyuni; Nur Syaqila; Fakhirah Naila Zalianty; Reni Handayani S; Nirwhana Yuliana Ahmad (www.amertainstitute.com, 2026)
This study examines the effect of Fixed Asset Turnover (FATO) on Return on Assets (ROA) among food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. The study is motivated by inconsistent empirical findings regarding the relationship between fixed asset efficiency and corporate profitability, particularly in the food and beverage industry. A quantitative associative research design was employed using secondary data obtained from annual financial reports published by the IDX and company websites. The sample was determined using purposive sampling, resulting in eight food and beverage companies with four years of observations, yielding 32 firm-year observations. Data were analyzed using descriptive statistics, classical assumption tests, simple linear regression, t-test, F-test, and the coefficient of determination (R²) with SPSS. The results indicate that FATO has a positive but statistically insignificant effect on ROA. The regression coefficient of FATO was 0.001, with a t-value of 1.138 and a significance level of 0.264, exceeding the 0.05 threshold. Furthermore, the R² value of 0.041 indicates that FATO explains only 4.1% of the variation in ROA, while the remaining 95.9% is attributable to other factors outside the research model. These findings suggest that fixed asset utilization alone is insufficient to explain profitability in the food and beverage sub-sector. Companies should therefore strengthen broader operational efficiency, cost control, pricing strategies, and asset management to improve profitability.